Identification of Tomato yellow leaf curl virus, Pepper huasteco yellow vein virus and Pepper golden mosaic virus associated with pepper diseases in northern Mexico. Issue 4 (2nd October 2019) - Morales-Aguilar, Juan J.; Rodríguez-Negrete, Edgar A.; Camacho-Beltrán, Erika; López-Luque, Cindy A.; Leyva-López, Norma E.; Jiménez-Díaz, Florencio; Voloudakis, Andreas; Santos-Cervantes, María E.; Méndez-Lozano, Jesús
Abstract: New diseases in pepper plantations were discovered in La Comarca Lagunera (CL) region in September 2014, the severity of which increased by October 2016. Pepper plants exhibited mild and severe yellow leaf mosaic, deformation, stunting and chlorotic leaves. In addition, whiteflies were observed on symptomatic plants, suggesting a possible begomovirus aetiology. In this study, naturally infected pepper plants were collected during three consecutive years to identify the potential begomovirus present in pepper in CL. PCR detection using degenerate and specific primers indicated that 47 out of 49 pepper plants were infected by begomoviruses mainly in mixed infection. The complete begomovirus genomes were isolated from a representative symptomatic pepper plant and two clones for each begomovirus were fully sequenced for the corresponding year of collection (2014 to 2016). Phylogenetic analysis of complete genomes of CL begomovirus pepper isolates indicated a close homology with Tomato yellow leaf curl virus (designated TYLCV-CL) displaying 99.9–100% identity with TYLCV Sinaloa isolate, and the bipartite Pepper huasteco yellow vein virus (designated PHYVV-CL) displaying 94.5% and 84.2% identity with first PHYVV isolate from Tamaulipas for DNA A and DNA B, respectively, and 97–98% identity with PHYVV Sinaloa isolate for DNA B. In 2016, Pepper golden mosaic virus (designated PepGMV-CL) was also found that consisted of DNA-A and DNA-B genome displaying 97% and 93.5% identity with PepGMV isolate Tamaulipas. To our knowledge, this is the first report of a pepper disease associated with TYLCV in double or triple infection either with PHYVV and/or PepGMV in Mexico.